Functional connectivity during masked and unmasked face emotion processing in bipolar disorder - Tseng, Wan-Ling (Psychiatry Res, 2016)
Little is known regarding the neural connectivity and correlates during automatic, unconscious face emotion processing in individuals with bipolar disorder (BD). In this study, 14 adults with BD and 14 healthy volunteers (HV) underwent fMRI scanning while completing an affective priming task with unconsciously perceived and consciously perceived faces (angry, happy, neutral, blank oval). We found that, regardless of awareness level and emotion types, BD patients exhibited diminished functional connectivity between amygdala and ventromedial prefrontal cortex (vmPFC) compared to HV. This connectivity finding is present in the absence of activation differences in amygdala. In addition, in medial frontal gyrus, BD patients displayed greater activation while HV displayed less activation to angry and neutral faces compared to no face. These results suggest that aberrant amygdala-vmPFC connectivity and neural dysfunction in areas implicated in appraisal and expression of emotions (medial frontal gyrus) may be the pathophysiological correlates of emotional processing in BD regardless of awareness level.